ANALYSIS OF ENTREPRENEURIAL SKILLS OF UNIVERSITY STUDENTS IN TERMS OF SOCIO-DEMOGRAPHIC CHARACTERISTICS: BATMAN UNIVERSITY VOCATIONAL COLLEGE RESEARCH - Ali Kemal CEYLAN (Fırat University, 2019)
From the emergence of industrial society to the today’s modern economic system, entrepreneurship has fulfilled an extremely important role. In today's socio-economic structure, which is conceptualized as information society, the importance of entrepreneur has increased even more. Enhancing and improving entrepreneurship, which is quite important for a country and society, has been one of the primary social purposes in recent years. It is a very important issue to investigate entrepreneurship in a multidimensional approach because of the crucial functions it perform within the economic system. The aim of this study is to measure the entrepreneurial skills of university students with high potential. For this purpose, by using simple random sampling method, a survey was conducted with among 393 students selected from Batman University Vocational College. In the questionnaire, the entrepreneurship scale composed of 36 items was used for the university students, which was developed by Yilmaz and Sünbül (2009). There were also 21 questions about the demographic characteristics of the students in the questionnaire. SPSS 17 program was used in the analysis of the data obtained from the research. In the reliability analysis of Yılmaz’s and Sünbül’s entrepreneurship scale, Cronbach Alpha reliability coefficient was found to be 0.90, which is quite high. As a result of the survey, the results obtained from the research revealed that the entrepreneurial skills of the university students were also high. This result is in general compatible with the results of the existing research literature. As a result of the research, the entrepreneurship of the students was tested by comparing with the demographic variables. T-Test and ANOVA analysis, which are parametric tests, were applied to the obtained data. On the basis of the results of this research, it can be concluded that universities should improve the quality of entrepreneurship education and more focus should be given to enhance entrepreneurial skills of university students with high entrepreneurial potential.